Monetary policy, neutrality and the environment - Jo\~ao Ricardo Faria; Peter McAdam; Bruno Viscolani (European Central Bank (ECB), 2021)
We study the interaction between monetary and fiscal policies in a Ramsey-Sidrauski model augmented with environmental capital. Equilibrium solutions are studied through the "Green Golden Rule". Despite the non-separability of money in utility and intertemporally nonseparable preferences, money is environmentally neutral. Policy impacts the environment via the marginal rate of transformation rather than the marginal rate of substitution between consumption and environment. Fiscal policies, lump sum and distortionary, under a balanced budget, are also environmentally non-neutral. Only under a non-balanced budget, when deficits are monetized, is money environmentally non-neutral. In alternative approaches (Cash-in- Advance, Transactions Costs), money is environmentally non-neutral.
Keywords: E52; E62; H23; 330; Ramsey-Sidrauski; Green Golden Rule; Environmental Capital; Chichilnisky et al. Conjecture; Cash in Advance; Transactions Costs; Friedman rule